Scientists: Four golden lessons - Weinberg, Steven (Himalayan Journal of Sciences, 2006)
After whizzing through undergraduate school, many students find themselves enmired in the endless suffering of a protracted degree program. Nobel Laureate Steven Weinberg (Physics 1979) dons his bodhisattva robes to impart four simple lessons that will help grad students in any field penetrate the fog of perceived reality. Briefly, these are -- but why should we spoil the fun? Weinberg’s lessons, and his prose, should be savored without intermediary.*Reprinted with permission from Nature, Vol 426, page 389, issue of 27 November 2003. Copyright © 2003 by Steven Weinberg. * Summary not from Nature; added with the permission by Himalayan Journal of SciencesThe full text is of this article is available at the Nature website